Relationship Between Institutional Shareholdings of the Constituent Companies of FTSE Islamic Index and Corporate Social Performance: An Empirical Investigation - Abul Hassan; Sofyan S Harahap (Indonesian Management and Accounting Research, 2006)
A business company which is defined as being socially responsible, demonstrates the perception of the link between social and fmancial performance. This characteristic may lead the business company to long-term competitive advantages in terms of improvement of financial performance. In the European countries, Islamic institutional investors such as mutual funds, equity funds, charities etc have become the predominant players and their influence in the western markets are growing. Present study hypothesises that Islamic or socially responsible institutional investors invest heavily in companies with strong corporate social performance. Empirical results indicate a significant, positive relationship between social performance and number of institutions holding shares of constituent companies of the Islamic index.